How does moral knowledge matter in development practice, and how can it be researched? - Fabian Scholtes (University of Bonn, Center for Development Research (ZEF), 2009)
This paper aims to contribute to a more comprehensive and balanced analysis of development practice. It does so by raising a neglected issue, in a perspective that explicitly targets the complexity of interaction in development. Based on a review of seminal contributions to Anthropology of Development, I suggest that the analysis of development practice needs to take into account the ambivalence of how moral norms and values influence interaction. The review shows how this ambivalence and complexity results from the structural conditions of development practice and the ways in which people relate to these conditions in their agency. To understand how and why development interaction occurs, research needs to capture this complexity. For this, I suggest conceiving of moral norms and values as a particular kind of knowledge. The paper elaborates this perspective conceptually and in terms of operationalisation. For the conceptual part, I draw upon anthropology of morality to show several aspects of moral knowledge, as well as problems of researching it. I also relate to anthropology of knowledge in order to conceive of moral knowledge in a more systematic manner. For the operationalisation part, I will exemplify some concrete research questions and hypotheses and raise some methodological issues of data collection and interpretation. The conclusion points to issues for further discussion, including substantive theories that allow for hypothesising about practice, methodological challenges of researching the practice of moral knowledge, and the generalisation of results.
urn:nbn:de:101:1-2009050587
Keywords: 300; Morality; values; knowledge; development practice; ways of knowing; anthropology